Edukasi Pengenalan Filosofi Warna dan Font Pada Desain Menggunakan Aplikasi Canva - Iwafani, Salwa Alif; Haes, Putri Ekarety (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
The Internet makes it easier for humans to communicate without being limited by space and time, one of which is designing using the Canva application. Therefore the purpose of community service activities (PKM) is to educate SMP Negeri 2 Susut, Abuan village, Bangli district, specifically to students and female users in class IX about the Canva application. There are three methods of introduction, implementation, and evaluation activities. In carrying out the activity, there were two sessions, namely the provision of materials and a workshop with the theme "Maintain Cleanliness by Not Throwing Trash Carelessly." From the community service activities carried out for partners, namely SMP Negeri 2 Susut class IX, Abuan village, Bangli district, they were very enthusiastic in participating in every activity, from providing material to using the Canva application on their respective smartphones.